Principal Radiographic Characteristics for Cervical Spinal Deformity: A Health-related Quality-of-life Analysis. Issue 18 (15th September 2017) - Bao, Hongda; Varghese, Jeffrey; Lafage, Renaud; Liabaud, Barthelemy; Diebo, Bassel; Ramchandran, Subaraman; Day, Louis; Jalai, Cyrus; Cruz, Dana; Errico, Thomas; Protopsaltis, Themistocles; Passias, Peter; et al.
Abstract : Study Design: Retrospective study. Objective: The aim of this study was to propose radiographic characteristics of patients with cervical disability and to investigate the relevant parameters when assessing cervical alignment. Summary of Background Data: Although cervical kyphosis is traditionally recognized as presentation of cervical deformity, an increasing number of studies demonstrated that cervical kyphosis may not equal cervical deformity. Therefore, several other differentiating criteria for cervical deformity should be investigated and supported with quality of life scores. Methods: A database of full-body radiographs was retrospectively reviewed. Patients without previous cervical surgery, with a well-aligned thoracolumbar profile (defined as T1 pelvis angle <15°), and with an available Neck Disability Index (NDI) score were reviewed in this study. Subjects were stratified into an asymptomatic (64 subjects with NDI ⩽15, Visual Analogue Scale [VAS] neck ⩽3, and VAS arm ⩽3) and a symptomatic group (107 subjects with NDI >15, VAS neck >3, or VAS arm >3). Independent t tests were performed to investigate differences between two groups. Logistic regressions and principal component analyses were then performed. Results: NDI averaged 5.43 in asymptomatic group, significantly smaller than symptomatic group (5.43 vs. 41.25). t Test revealed that C2-C7 sagittal vertical axis (SVA), McGregor slope, and the slope of line of sight (SLS) were significantly different while C2-C7 angle (cervical curvature, CC) did not show statistical difference ( P = 0.09). Logistic regressions were performed using the significantly different parameters as well as CC. Results identified C2-C7 SVA and SLS as independent risk factors for low health-related quality of life. The principal component analysis leads to a new factor (0.55 × C2C7SVA + 0.34 × COC2 + 0.77 × CC) with strong correlations with NDI, VAS, and EQ5D measurements. Conclusion: The traditional concept of cervical kyphosis should not be regarded as a standalone criterion of cervical deformity. The most clinically relevant components of cervical analysis are the C2-C7 SVA, C0C2 angle, and C2C7 angle. In addition, the three components should be assessed together in harmony and not individually. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the text